A Substudy Evaluating Treatment Intensification on Medication Adherence among Hypertensive Patients Receiving Home Blood Pressure Telemonitoring and Pharmacist Management - Pawloski, Pamala A. (J Clin Pharm Ther, 2016)
WHAT IS KNOWN AND OBJECTIVE: Hypertension is a leading cause of death and major contributor to heart attacks, strokes, heart and kidney failure. Anti-hypertensive (HTN-medication) non-adherence contributes to uncontrolled hypertension. Effective initiatives to improve uncontrolled hypertension include a team-based approach with home blood pressure (BP) monitoring. Our study objective was to evaluate whether objectively measured medication adherence was influenced by home BP telemonitoring and pharmacist management. METHODS: We analyzed HTN-medication adherence in 240 patients who received home BP telemonitoring and pharmacist intervention (TI). Adherence was measured based on prescription fills and the proportion of days covered (PDC). HTN-medications continued pre- to post-baseline was similar for telemonitoring intervention (TI) and usual care (UC) patients (rate ratio=1.00, p=0.90). RESULTS AND DISCUSSION: More HTN-medications were discontinued pre- to post-baseline in TI patients (rate ratio=1.38, p=0.04). Similarly, more HTN-medications were added in TI patients (rate ratio=2.46, p<0.001). The proportion with a mean PDC>=0.8 for HTN-medications added after baseline and overall adherence did not differ between groups. WHAT IS NEW AND CONCLUSION: Medication adherence was high in both groups; however, medication adherence was not significantly altered by the intervention. There were more medication modifications and greater medication intensification among TI patients.